Transcription and cancer. - Cox, P; Goding, C (1991)
The normal growth, development and function of an organism requires precise and co-ordinated control of gene expression. A major part of this control is exerted by regulating messenger RNA (mRNA) production and involves complex interactions between an array of transcriptionally active proteins and specific regulatory DNA sequences. The combination of such proteins and DNA sequences is specific for given gene or group of genes in a particular cell type and the proteins regulating the same gene may vary between cell types. In addition the expression or activity of these regulatory proteins may be modified depending on the state of differentiation of a cell or in response to an external stimulus. Thus, the differentiation of embryonic cells into diverse tissues is achieved and the mature structure and function of the organism is maintained. This review focusses on the role of perturbations of these transcriptional controls in neoplasia. Deregulation of transcription may result in the failure to express genes responsible for cellular differentiation, or alternatively, in the transcription of genes involved in cell division, through the inappropriate expression or activation of positively acting transcription factors and nuclear oncogenes. Whether the biochemical abnormalities that lead to the disordered growth and differentiation of a malignant tumour affect cell surface receptors, membrane or cytoplasmic signalling proteins or nuclear transcription factors, the end result is the inappropriate expression of some genes and failure to express others. Current research is starting to elucidate which of the elements of this complicated system are important in neoplasia.